Analisis Studi Kelayakan Aspek Pemasaran Pada Industri Pengolahan Apel : Kasus Permata Agro Mandiri di Kota Batu - Hidayah, Nurul; Sonia, Lailatul Izzah; Solekah, Nihayatu Aslamatis (Maliki Interdisciplinary Journal, 2025)
This study aims to analyze the marketing strategies of PT Permata Agro Mandiri, a local apple processing company based in Batu City. Utilizing apples as its main raw material, the company produces various processed goods such as apple pies, which serve as unique souvenirs of the city. Batu City, known as a premier tourist destination, offers significant opportunities to market these products to both local and international tourists. Digital marketing strategies have been implemented through platforms like Facebook, Shopee, and Tokopedia to expand market reach. However, challenges arise from intense competition with similar products, fluctuating raw material prices, and evolving consumer trends. The company is advised to enhance marketing innovation by leveraging new social media platforms such as TikTok, creating creative promotional content, and collaborating with influencers to capture consumer attention. Additionally, the integration of attractive and modern packaging emphasizes the product's premium value. The study reveals that PT Permata Agro Mandiri has substantial potential for further growth by optimizing digital strategies while maintaining product quality. With a sustainable and innovative approach, the company not only secures its market position but also contributes to promoting local tourism and economic development.